Developing and Implementing ICF-Based Tools for Occupational Rehabilitation Supporting the Communication and Return to Work Process Between Sickness Absentees, Clinical Team and Jobcentre Contacts - Johansen, Thomas; Kvaal, Astrid Marie; Konráðsdóttir, Ása Dóra (Frontiers in Rehabilitation Sciences, 2022)
Background: The ICF model is applied as a conceptual framework in occupational rehabilitation in Norway. Objective: To systematically apply the model in rehabilitation this study had the following aims: 1) apply an ICF subset by merging an ICF core set and an ICF set to assess functioning in rehabilitation patients related to work; 2) develop a patient-reported ICF questionnaire and a clinician-friendly ICF report complementing the ICF subset assessment; and 3) evaluate whether ICF-based tools (subset, questionnaire, report) support the communication between a clinical team, patient and jobcentre contacts in return to work (RTW) follow up. Methods: 41 patients completing four weeks rehabilitation were recruited. The patients were referred from general practitioners or jobcentres. The ICF subset was a combination of the EUMASS core set for disability evaluation and suggested ICF categories by experts in vocational rehabilitation from Iceland. A clinical team interviewed the patients using the ICF subset and problems were quantified on a generic qualifier scale for body functions, activities and participation and environmental factors. The research team and clinical team developed an ICF questionnaire, by cross-culturally adapting the Work Rehabilitation Questionnaire to Norwegian. The same teams also developed an ICF report. The rehabilitation clinic forwarded the report and questionnaire to the patients’ jobcentre contact, which was responsible for the RTW follow up. To evaluate the benefits of ICF-based tools, the clinical team, user representative and jobcentre contacts together participated in four workshops. They were asked the degree to which and in what way the tools supported the communication between them. Results: The ICF subset captured RTW challenges but was found to be time consuming. The jobcentres experienced the ICF report and questionnaire beneficial in the follow up as it strengthened RTW decision-making basis and communication with the rehabilitation clinic and the patients about work-related interventions. Conclusions: The development and integration of ICF-based tools for clinical practice was a preliminary success in supporting the communication between three stakeholders during RTW follow up. Future applications of ICF tools ought to integrate personal factors to capture both facilitators and barriers related to functioning and work contributing to a holistic assessment.